Development of downtime cost calculator for offloading operations influenced by parametric rolling - Patel, M.S. (MDPI AG, 2020)
The stability of FPSO or offloading shuttle tanker may be affected in wave conditions which excite parametric rolling. The offloading operations are thereby ceased and eventually leads to loss in production which affects the revenue of global production, better known as downtime cost. This paper discusses downtime cost analysis of offloading operations due to parametric rolling of shuttle tanker under regular waves in Malaysian waters for three different locations. The downtime due to parametric rolling is investigated for two different water depths for which the probability of occurrence was calculated from the location specific wave scatter diagram. The results of parametric rolling of shuttle tanker along with downtime cost charts are presented. Additionally, a Graphical User Interface (GUI) was developed and its work procedure is demonstrated in this paper. The down-time cost calculator will help the oil operator companies to analyze the economic risks involved for field developments and anticipate the loss in revenue for downtime occurrences. The developed GUI was copyrighted under literary work as intellectual property. Â© 2019 by the authors.